2022
DOI: 10.1101/gr.276747.122
|View full text |Cite
|
Sign up to set email alerts
|

Listeria monocytogenes genes supporting growth under standard laboratory cultivation conditions and during macrophage infection

Abstract: The Gram-positive bacterium Listeria monocytogenes occurs widespread in the environment and infects humans when ingested along with contaminated food. Such infections are particularly dangerous for risk group patients, for whom they represent a life-threatening disease. To invent novel strategies to control contamination and disease, it is important to identify those cellular processes that maintain pathogen growth inside and outside the host. Here, we have applied transposon insertion sequencing (Tn-Seq) to L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 119 publications
0
16
0
Order By: Relevance
“…In B. subtilis , WalRK also regulates the expression of genes involved in WTA biosynthesis and export ( Howell et al, 2003 ). The regulon of the WalRK system has not yet been determined for L. monocytogenes , however, it was shown that the system is essential ( Fischer et al, 2022 ). Inactivation of WalRK usually leads to cell death of wildtype cells due to loss of peptidoglycan hydrolase activity, however, cell death could be prevented by the inhibition of peptidoglycan biosynthesis ( Salamaga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In B. subtilis , WalRK also regulates the expression of genes involved in WTA biosynthesis and export ( Howell et al, 2003 ). The regulon of the WalRK system has not yet been determined for L. monocytogenes , however, it was shown that the system is essential ( Fischer et al, 2022 ). Inactivation of WalRK usually leads to cell death of wildtype cells due to loss of peptidoglycan hydrolase activity, however, cell death could be prevented by the inhibition of peptidoglycan biosynthesis ( Salamaga et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…We compared the cgMLST and accessory genome MLST (agMLST) allele annotations of the 1,802 isolates with a previously generated list of L. monocytogenes cg/agMLST alleles affected by internal stop codons (44). As the cg/agMLST algorithm annotates frameshifted alleles as "failed" alleles, we also inspected the cg/agMLST alleles for the occurrence of failed alleles that are associated with particular sequence types or even specific cgMLST clusters.…”
Section: Identification Of Premature Stop Codonsmentioning
confidence: 99%
“…The foundation of data is laid by the genome annotation of L. monocytogenes strain EGD-e (RefSeq accession: NC_003210.1) (Toledo-Arana et al, 2009). Gene essentiality and gene expression data were obtained from published information (Camejo et al, 2009; Fischer et al, 2022). Using specific PubMed queries, 1,285 publications were added as relevant references to the Gene pages.…”
Section: Implementation and Datamentioning
confidence: 99%
“…Currently, global analyses on protein-protein interactions between L. monocytogenes proteins or even on the interactions of L. monocytogenes proteins with the host proteome are not available. Likewise, the determination of essential gene sets under varying conditions has just started recently (Fischer et al, 2022; Wu et al, 2022). When information on gene essentiality in different mutant backgrounds becomes available one day, implementation and visualization of such synthetic lethal interactions could possibly be a useful extension.…”
Section: Future Perspectivesmentioning
confidence: 99%